CircAMOTL1 Promotes Tumorigenesis Through miR-526b/SIK2 Axis in Cervical Cancer - Sun, Zhengwei; Niu, Sanqiang; Xu, Fuxia; Zhao, Weidong; Ma, Rong; Chen, Mingwei (Frontiers in Cell and Developmental Biology, 2020)
Background Cervical cancer is one of the most common malignancies in women, leading to major health problems for its high morbidity and mortality. Numerous studies have demonstrated that circular RNAs (circRNAs) could be participated in the progression of multifarious diseases, especially plentiful carcinomas. CircAMOTL1 (angiomotin-like1, ID: hsa_circ_0004214), which is located on human chromosome 11:9 4532555-94533477, is involved in the occurrence of breast cancer, etc. However, the intrinsic and concrete molecular mechanism of circAMOTL1 in cervical carcinomas remained thoroughly unclear, which was also the bottleneck of circRNAs studies in cancer. Methods The relative expression levels of circAMOTL1 and miR-526b in cervical carcinoma patients’ specimens and cervical carcinoma cell lines were detected by RT-qPCR. Through experiments including loss-function and overexpression, the biological effects of circAMOTL1 and miR-526b on the proliferation, migration, apoptosis, and tumorigenicity were explored in cervical carcinomas. Dual luciferase reporter gene analysis, western blot, and other methods were adopted to explore the circAMOTL1 potential mechanism in cervical carcinomas. Results In our experiments, our researches displayed that circAMOTL1 was significantly higher expression in cervical carcinomas specimens and cell lines. Further experiments illustrated that the knockdown of circAMOTL1 could restrain the malignant phenotype, AKT signaling, and epithelial–mesenchymal transition (EMT) of in cervical carcinomas cells. Meanwhile miR-526b was downregulated in cervical carcinomas and even miR-526b could partially reverse circAMOTL1 function in malignant cervical tumor cells. CircAMOTL1 acts as a microRNA (miRNA) sponge that actively regulates the expression of salt-inducible kinase 2 (SIK2) to sponge miR-526b and subsequently increases malignant phenotypes of cervical carcinomas cells. In a word, circAMOTL1 acts a carcinogenic role and miR-526b serves as the opposite function of antioncogene in the cervical carcinoma pathogenesis. Conclusion CircAMOTL1-miR-526b-SIK2 axis referred to the malignant progression and development of cervical carcinomas. CircAMOTL1 expression was inversely correlated with miR-526b and positively correlated with SIK2 mRNA in cervical cancer tissues. Thus, circAMOTL1 exerted an oncogenic role in cervical cancer progression through sponging miR-526b. Taken together, our study revealed that circAMOTL1 acted as an oncogene and probably was a potential therapeutic target for the cervical cancer.